Emotional Intelligence and Conflict Management in Healthcare - Theodoratou, Maria; Papadopoulos, Andreas; Megari, Kalliopi; Tsitsas, George; Andriopoulou, Panoraia (International Conference on Business and Economics - Hellenic Open University, 2025)
This study explores the relationships among Emotional Intelligence (EI), psychological distress, and conflict management in healthcare professionals, incorporating demographic and occupational factors. A cross-sectional quantitative design was employed with a sample of 143 healthcare professionals from various specialties in Greece. Emotional Intelligence was measured using the NHS EI Leadership Tool, psychological distress with the Kessler K6+ scale, and conflict management with McClellan’s Conflict Resolution Questionnaire. Statistical analyses revealed that EI was a significant positive predictor of effective conflict management, while psychological distress negatively impacted conflict resolution. Age and professional specialty moderated these relationships, with older professionals and psychologists demonstrating higher conflict management scores. The findings underscore the importance of Emotional Intelligence in fostering constructive workplace dynamics and reducing psychological distress in healthcare settings. JEL Classifications: I19, M12, M14 Keywords: Emotional Intelligence, Psychological Distress, Conflict Management, Healthcare Professionals